An experimental assessment of social tolerance and den ecology in a high-density octopus population - Duncan A. O’Brien; Michelle L. Taylor; Heather D. Masonjones; Philipp H. Boersch-Supan; Owen R. O’Shea (Marine Biology, 2021)
Long held notions of the universally asocial octopus are being challenged due to the identification of high-density and interacting octopus populations in Australia, Indonesia, Japan and the deep sea. This study experimentally assessed the social tolerance and presence of potential prey items of Caribbean reef octopus , Octopus briareus, in a tropical marine lake (25°21′40″N, 76°30′40″W) on the island of Eleuthera, The Bahamas, by deploying artificial dens in multi-den groups or ‘units’ in the months of May and June 2019. Fifteen octopus were observed occupying dens ( n = 100), resulting in 13 den units being occupied ( n = 40). Two examples of adjacent occupation within a single den unit were identified but with zero examples of cohabitation/den sharing. Ecological models showed den and den unit occupation was predicted to increase with depth and differ between sites. Octopus also displayed no preference for isolated or communal units but preferred isolated dens over dens adjacent to others. Additionally, 47 % of occupied dens contained bivalve or crustacean items with no epifauna on their interior surface. The lack of epifauna suggests that these items have been recently ‘cleaned’ by occupying octopus and so represent likely prey. This study presents evidence of possible antisocial den use by O. briareus , a modification of the default ‘asocial’ ignoring of conspecifics typically attributed to octopus. This is likely in response to the high population density and may imply behavioural plasticity, making this system appropriate for further scrutiny as a research location on the influence of large, insular environments on marine species.